BUDIDAYA IKAN LELE DAN DIVERSIFIKASI PRODUK OLAHAN IKAN LELE DI PESANTREN PUTRA PUTRI YATIM DARUL AITAM DESA BANJARAGUNG JATIAGUNG LAMPUNG SELATAN - Indariyanti, nur; Purbosari, Ninik; Febriani, Dian; Verdian, Aldi Huda (Politeknik Negeri Lampung, 2022)
Darul Aitam Yatim Islamic Boarding School is an educational and social institution for orphans, aiming to provide adequate housing and education for orphans and try to meet their needs well. The boarding school is located in Banjaragung Village, Jatiagung District, South Lampung Regency, Lampung Province. The number of students at the end of 2020 was 248 students. The purpose of this service activity is to increase the knowledge, insight, and skills/skills of the students at the Putra Putri Yatim Darul Aitam Islamic Boarding School by providing training on catfish cultivation in buckets for male students and training on making processed catfish-based products (fish nuggets, fish balls, sempol fish, fish rolls) for female students. The method used is the lecture method, practice, discussion, and question and answer. The achievements of service activities at the Darul Aitam Putra Putri Yatim Islamic Boarding School include the enthusiasm of male and female students in participating in very high activities, can provide entrepreneurial motivation as a strengthening of independent business, and can increase knowledge, insight, and skills/skills for processing catfish-based products for female students and for male students they can cultivate catfish in buckets for entrepreneurship.